ANALISIS KELAYAKAN PENCADANGAN KAWASAN SHRIMP ECO-FARMING DI KABUPATEN PINRANG - Sitti Marhamah Syam; Muhammad Hattah Fattah; Muhammad Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
The increasing global market demand is an opportunity for the development and improvement of the eco-shrimp category of Penaeus monodon. The global market demands for producing eco-shrimp shrimp and the application of EAA (Ecology Aquaculture Area), initiated the establishment of the Shrimp Eco-farming Park area in Pinrang Regency. The Minapolitan Lowita area in Lanrisang Subdistrict is an expansion of the Minapolitan Lowita Area in Suppa Subdistrict, agreed upon as a development area for tiger shrimp (Penaeus monodon) oriented to the Shrimp Eco-farming Park in Pinrang Regency. This study aims to analyze the level of the feasibility of ponds in Lanrisang District to be reserved for the Shrimp Eco-farming Park Region of Pinrang Regency. The study was conducted in Lanrisang District, Pinrang Regency from April 2017 to March 2018. The research method was by observation and analysis of test samples. The number of test samples was 12 samples, taken at 12 locations during the rainy season and dry season. The parameters measured were aquatic biophysics (water quality, soil quality, topography, rainfall, and tides) during the rainy season and dry season. Feasibility analysis uses a weighting system and suitability parameter scores. The results showed: the level of the feasibility of the pond was very suitable during the rainy season (8.45) and the level of the feasibility of the pond was suitable in the dry season (7.15).